Anti-Candida Activity of Extracts Containing Ellagitannins, Triterpenes and Flavonoids of Terminalia brownii, a Medicinal Plant Growing in Semi-Arid and Savannah Woodland in Sudan - Enass Y. A. Salih; Riitta Julkunen-Tiitto; Olavi Luukkanen; Pia Fyhrqvist (MDPI AG, 2022)
Various parts of Terminalia brownii (Fresen) are used in Sudanese traditional medicine against fungal infections. The present study aimed to verify these uses by investigating the anti-Candida activity and phytochemistry of T. brownii extracts. Established agar diffusion and microplate dilution methods were used for the antifungal screenings. HPLC-DAD and UHPLC/QTOF-MS were used for the chemical fingerprinting of extracts and for determination of molecular masses. Large inhibition zones and MIC values of 312 µg/mL were obtained with acetone, ethyl acetate and methanol extracts of the leaves and acetone and methanol extracts of the roots. In addition, decoctions and macerations of the leaves and stem bark showed good activity. Sixty compounds were identified from a leaf ethyl acetate extract, showing good antifungal activity. Di-, tri- and tetra-gallotannins, chebulinic acid (eutannin) and ellagitannins, including an isomer of methyl-(S)-flavogallonate, terflavin B and corilagin, were detected in T. brownii leaves for the first time. In addition, genipin, luteolin-7-O-glucoside, apigenin, kaempferol-4'-sulfate, myricetin-3-rhamnoside and sericic acid were also characterized. Amongst the pure compounds present in T. brownii leaves, apigenin and β-sitosterol gave the strongest growth inhibitory effects. From this study, it was evident that the leaf extracts of T. brownii have considerable anti-Candida activity with MIC values ranging from 312 to 2500 µg/mL.